Psychological Distress Among Chinese College Students During the COVID-19 Pandemic: Does Attitude Toward Online Courses Matter? - Yueyun Zhang; Baozhong Liu (Frontiers in Psychology, 2021)
Due to the pandemic of coronavirus disease 2019 (COVID-19), taking online courses has become a “new normality” for college students. This study paid particular attention to the role of college students’ attitude toward online courses (ATOC) in shaping their psychological distress during the COVID-19 epidemic in China. Participants were from a national panel survey that has been administered before and during the COVID-19 epidemic. Besides bivariate analysis, a multivariate regression model while adjusting for a lagged dependent variable (i.e., pre-COVID distress) was estimated to show the association between ATOC and during-COVID distress. We found that respondents from a disadvantaged family background (i.e., below-college parental education, below-average family economic condition, and rural residence) were more likely to have an “unsupportive” ATOC. Moreover, both bivariate and multivariate analyses confirmed that respondents with a “neutral” or “unsupportive” ATOC had greater during-COVID psychological distress, compared to their counterparts with a “supportive” ATOC. Given the persistent spread of the COVID-19 worldwide and the profound onsite-online transition in course delivery in higher education, students’ perceptions and evaluations of the massive online courses should be carefully considered and integrated into curriculum reforms in both present and post COVID-19 situations.